The computer support of diagnostics of circle crystallizers - J. David; P. Švec; R. Frischer; R. Garzinova (Metalurgija, 2014)
This paper is focused on computer aided technological processes of continuous steel casting devices. The paper characterized the fundamental aspects of creating computer aided control process of continuous steel casting operations. There is in detail described software system AMKO (Algorithm Modelling conicities). The importance of software AMKO consists in extending the usability of copper enclosure in the case of its weariness and the possibility of its further use. Using this software to create graphical model of the wear, which shows the conicity of the studied mold along all its lengths and specifies the possibility of its further use in various compositions sequences. Such modelling and prediction is possible with usage of cybernetic modelling principles and methods known as soft-computing.